Rubber Ball Media Improves Basic Heading Movements In Football Games - Riki Hidayat; Eko Prabowo; Dena Widyawan (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. At SD Plus Silmi Ramadhan, Bekasi Regency, a research study was conducted to enhance the learning outcomes of basic football movements, specifically heading, in grade 6 students. Rubber balls were utilized as a medium during the learning process to provide an effective and safe environment for the students to practice and improve their skills. The study aimed to develop the student's proficiency in the game of football and enable them to perform the necessary basic movements with ease and accuracy. Material and Method. The research conducted was on the classroom action type, commonly known as PTK, which stands for Pembelajaran Tindakan Kelas in Indonesian. The method used to collect and analyze data was quantitative descriptive, which is a research method that focuses on describing the characteristics of a population. The sample group consisted of 6th-grade students who attended SD Plus Silmi Ramadhan, located in Bekasi Regency. The data collection procedure involved administering a pre-test to the students before the research began to determine their knowledge level and learning outcomes for cycle 1. Result. According to the results of the study, the average score during the first cycle was 83.5. However, the post-test showed a significant increase in the scores compared to the first cycle. This suggests that the participants made progress and improved their performance over time. Conclusion. At SD Plus Silmi Ramadhan Serang Baru, Bekasi Regency, grade 6 students are struggling with basic heading techniques in football games. Despite the efforts made by their teachers, students still use incorrect and ineffective techniques, leading to poor learning outcomes. Hence, researchers have taken up the task of finding a solution to overcome this challenge. By conducting thorough research and analysis, they aim to identify the root cause of this problem and develop effective strategies to improve the learning outcomes of students in basic heading techniques in football games.